Psychosomatic medicine - Ackerman, Kurt; DiMartini, Andrea F. (Pittsburgh pocket psychiatry series., 2015)
Psychosomatic Medicine (PM) is a rapidly developing subspecialty of psychiatry focusing on psychiatric care of patients with other medical disorders. PM specialists diagnose and manage psychiatric symptoms in a variety of medical settings, optimize their patients' medical care, and expand understanding regarding the role of psychological factors in health and disease. PM practitioners may function as psychiatric consultants in hospital-based wards, primary providers in med-psych units, or collaborative practitioners integrated with inpatient and outpatient medical teams.